1997
DOI: 10.1007/bf02465095
|View full text |Cite
|
Sign up to set email alerts
|

Morphologische Korrelation der funktionellen Bauchwandmechanik nach Mesh-Implantation

Abstract: Modern surgical hernia repair depends increasingly on synthetic meshes for reconstruction of the abdominal wall. Despite the undisputed advantages of the synthetic meshes currently available, reports of late complications after implantation are accumulating. It is essential that the synthetic meshes be improved, but this makes a standardized animal model necessary for evaluation of their biocompatibility on both functional and morphological levels. In the present study, commercially available polypropylene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 7 publications
0
8
0
4
Order By: Relevance
“…These findings indicate an improved biocompatibility of PVDF towards the other materials. Since this was also found in other studies for PVDF as a mesh component [21,22,23], it is a new finding concerning monofilamental PVDF sutures. Vicryl induced a CTI which was greater than in other filaments.…”
Section: Discussionmentioning
confidence: 70%
“…These findings indicate an improved biocompatibility of PVDF towards the other materials. Since this was also found in other studies for PVDF as a mesh component [21,22,23], it is a new finding concerning monofilamental PVDF sutures. Vicryl induced a CTI which was greater than in other filaments.…”
Section: Discussionmentioning
confidence: 70%
“…The CTI was longer in case of thicker sutures and even increased over time. If its length approaches a plateau after 21 days as described in other studies on mesh materials, in which the inflammatory activity seems to be widely constant after day 21 [5], it has to be clarified in further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired biocompatibility leads to extended foreign body response. The more active a foreign body reaction and the more extended the granuloma, the more fragile will be the surrounding tissue, which is a decisive feature for foreign body migration [5,6]. An excellent biocompatibility is indicated by a small diameter of the granuloma with few inflammatory cells [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These consequences of the biological response to the foreign material are markedly influenced by the amount of incorporated material, particularly depending on the surface and the pore size. 5,6 Theoretical considerations, as well as the intraoperatively measured tensile strength during hernia repair, indicate that most of the currently available mesh materials are oversized with inappropriate elastic properties. 7 Both animal experiments and clinical experience have shown that adapting the mesh to the physiological demands by reducing the amount of introduced material (amount of polypropylene Ͻ 30 g/m 2 ) and enlarging the pore size (as in a multifilament low-weight mesh) results in a significant improvement in biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Both animal experiments 7 and clinical studies 8 show reduced functional impairment and a lowered periprosthetic inflammation with material-reduced meshes. Unfortunately, the construction of large-pore-size, low-weight meshes requires the use of multifilaments to prevent an inappropriate stiffness of the textile material.…”
mentioning
confidence: 96%